(untitled) (Global Journal of Management and Business Research, 2011)
Abstracts -India is one of the fastest growing markets of the world. The potential not only lies in the urban India but in the rural India also. The study has been carried out to differentiate the buying behaviour of rural households from that of urban households. Three durable goods from three different product categories; Television (entertainment product), Refrigerator (home appliance), and an Automobile (twowheeler, motorcycle and car/jeep) have been selected for study. A sample of 411 (204 from urban and 207 from rural areas) households across the Punjab state (India) have been selected on the basis of nonprobability convenience sampling. Overall no significant differences could be observed between rural and urban consumers in terms of their; timing of purchase, buying the same brand of other durable, number of items, and duration of planning before buying. Habitat (rural or urban) has a relation with income for the timing of buying a television, refrigerator, and automobile except in case of buying of an automobile on festive / special occasion, where the income had no relation with habitat. There is a relation between habitat and income in terms of duration of planning for different time periods before the buying of a television and refrigerator. The habitat also reveals association with income in terms of planning for months before buying an automobile. No association has been observed between habitat and income in case of planning for few days, few weeks and years before buying an automobile.